A gel electrolyte, its preparation method and use
Patent Information
- Application Number
- CN202611293762.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-09-25
AI Technical Summary
[0007]本发明的主要目的是提供一种凝胶电解质及其制备方法和应用,旨在解决现有电解质如何兼具高安全性和高机械强度的问题
[0023](1)本发明仅需将各组分在室温下混合均匀,注入模具后一步热引发聚合即可成型,全程无需紫外光照、溶剂蒸发或复杂涂覆设备,能耗低、易于规模化生产。以离子液体作为唯一溶剂,完全摒弃有毒有害有机溶剂(如DMF、NMP、碳酸酯类),避免了溶剂回收和干燥工序,符合绿色化学理念,显著降低生产成本和环境负担。
Smart Images

Figure CN122822873A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery technology, and in particular to a gel electrolyte, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries have been widely used in portable electronic devices, electric vehicles, and energy storage systems due to their high energy density and long cycle life. However, traditional lithium-ion batteries use liquid organic electrolytes (such as carbonate solvents), which pose serious safety hazards such as flammability, explosiveness, and leakage. In particular, the frequent battery fires and explosions in recent years have greatly restricted their application in large-scale energy storage and high-energy-density scenarios.
[0003] To address the aforementioned safety concerns, solid-state electrolytes are considered one of the most promising alternatives. Among them, gel polymer electrolytes (GPEs) have attracted widespread attention due to their combination of the high ionic conductivity of liquid electrolytes and the good processability of solid electrolytes. GPEs typically consist of a polymer matrix, lithium salt, and organic solvent, with the liquid electrolyte immobilized within the polymer matrix, thus reducing the risk of leakage to some extent. However, existing GPEs still face two major challenges: firstly, insufficient mechanical strength, making it difficult to effectively suppress short circuits caused by lithium dendrite penetration; and secondly, the organic solvents used remain flammable, failing to fundamentally eliminate the fire hazard.
[0004] To address the aforementioned issues, researchers have undertaken various attempts. Existing technology CN115207461A discloses a flame-retardant flexible composite gel electrolyte material. This material improves the mechanical properties and ionic conductivity of the electrolyte by introducing solid lithium lanthanum zirconium aluminum tantalum oxide ceramic nanofibers as inorganic fillers and combining them with photoinitiated polymerization. Simultaneously, it utilizes plasticizers (such as triethyl phosphate) to impart a certain degree of flame retardancy. However, this approach still relies on traditional carbonate solvents as plasticizers, and the photoinitiated polymerization process requires sophisticated equipment, hindering large-scale production. Furthermore, its flame-retardant effect depends on free small-molecule plasticizers, and there remains a risk of electrolyte leakage if the battery is damaged.
[0005] Another existing technology, CN120319881A, proposes a gel solid electrolyte based on silazane polymer monomers. Through in-situ copolymerization of silazane and ester crosslinking agents, it effectively binds strong Lewis acids (such as PF5) and hydrofluoric acid (HF), thereby improving the cycle stability of high-voltage silicon-based / lithium metal batteries. While this approach achieves progress in acid binding and high-voltage tolerance, its solvent system is still mainly based on traditional carbonates and requires the addition of a large amount of fluorinated diluents (such as TTE), failing to completely solve the electrolyte's flammability problem. Furthermore, its mechanical performance improvement mainly relies on the polymer network itself, lacking a reinforcement design to address lithium dendrite penetration.
[0006] In summary, existing gel electrolyte technologies have not yet achieved a good balance between safety (flame retardancy, puncture resistance) and overall electrochemical performance. There is an urgent need to develop a new type of gel electrolyte that is simple to prepare and has both ultra-high mechanical strength and inherent flame retardant properties to meet the needs of next-generation high-safety lithium batteries. Summary of the Invention
[0007] The main objective of this invention is to provide a gel electrolyte, its preparation method, and its application, aiming to solve the problem of how existing electrolytes can simultaneously achieve high safety and high mechanical strength.
[0008] To achieve the above objectives, the present invention provides a method for preparing a gel electrolyte, the method comprising the following steps:
[0009] Step 1: Mix lithium salt, polymer, polymer monomer, crosslinking agent, thermal initiator and ionic liquid at room temperature and stir until completely dissolved to obtain a precursor solution. The ionic liquid is selected from one or more imidazole ionic liquids. The precursor solution does not contain organic solvents.
[0010] Step 2: Inject the precursor solution obtained in Step 1 into the mold;
[0011] Step 3: Place the mold containing the precursor solution in an oven at 40℃~100℃ for thermally initiated polymerization to obtain a gel electrolyte with a chemically cross-linked network.
[0012] Optionally, in step 1, the precursor solution comprises 10% to 40% lithium salt, 0.1% to 5% polymer, 1% to 30% polymer monomer, 0.01% to 0.1% crosslinking agent, 0.1% to 2% initiator, and the remainder is ionic liquid.
[0013] Optionally, the lithium salt comprises one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluoroborate oxalate, lithium dioxalate borate, and lithium 4,5-dicyano-2-trifluoromethylimidazolium.
[0014] Optionally, the polymer comprises one or more of polyethylene oxide, polyethylene glycol, polyacrylic acid, and polyvinyl alcohol.
[0015] Optionally, the polymer monomer includes one or more of acrylamide, N-hydroxyethylacrylamide, acrylic acid, methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, 2,2,2-trifluoroethyl-methacrylate, 2,2,3,3,3-pentafluoropropyl-methacrylate, 2-methoxyethyl acrylate, glycidyl methacrylate, dimethyl vinyl phosphate, diethyl vinyl phosphate, and dibutyl vinyl phosphate.
[0016] Optionally, the crosslinking agent includes one or more of N,N'-methylenebisacrylamide, polyethylene glycol diacrylate, and glutaraldehyde.
[0017] Optionally, the thermal initiator comprises one or more of azobisisobutyronitrile, ammonium persulfate, potassium persulfate, and tert-pentyl peroxide.
[0018] Optionally, in step 1, the stirring time is from 10 minutes to 12 hours.
[0019] Optionally, in step 3, the baking time is from 30 minutes to 6 hours.
[0020] In addition, to achieve the above objectives, the present invention also provides a gel electrolyte, which is prepared by any of the methods described above.
[0021] In addition, to achieve the above objectives, the present invention also provides a lithium-ion battery comprising the gel electrolyte described above.
[0022] Beneficial effects:
[0023] (1) This invention only requires mixing all components evenly at room temperature, injecting them into a mold, and then performing a one-step thermally initiated polymerization to form the product. The entire process does not require ultraviolet light, solvent evaporation, or complex coating equipment, resulting in low energy consumption and easy large-scale production. Using ionic liquid as the sole solvent completely eliminates toxic and harmful organic solvents (such as DMF, NMP, and carbonates), avoiding solvent recovery and drying processes, which is in line with the concept of green chemistry and significantly reduces production costs and environmental burden.
[0024] (2) The polymer and chemical cross-linked network of the present invention form a semi-interpenetrating network structure, which synergistically endows the gel electrolyte with extremely high toughness and puncture resistance. The tensile strength can reach more than 16 MPa and the elongation at break exceeds 800%, which can effectively inhibit lithium dendrite puncture. As the only liquid phase component that is non-flammable and low-volatility, the ionic liquid ensures that the gel electrolyte does not ignite or spread under open flame. The battery using this electrolyte does not smoke or expand in the nail penetration test, and its safety is significantly better than that of traditional liquid electrolytes.
[0025] (3) Ionic liquids provide continuous and efficient ion transport channels, in which lithium salts are fully dissociated, and polymer polar groups assist in the hopping conduction of lithium ions, giving the gel electrolyte both high ionic conductivity and a wide electrochemical window, making it compatible with high-voltage cathode materials. It does not contain easily decomposable fluorinated carbonates and other additives, reducing interfacial side reactions, and has good compatibility with lithium metal anodes, which helps to extend battery cycle life.
[0026] (4) Through optimized component design and simple preparation process, the present invention has successfully achieved synergistic improvement in mechanical strength, safety performance and electrochemical performance of gel electrolyte; it can be widely used in the field of high safety lithium-ion batteries. Attached Figure Description
[0027] Figure 1 This is a schematic flowchart of an embodiment of a method for preparing a gel electrolyte according to the present invention.
[0028] Figure 2 The stress-strain curve of the gel electrolyte prepared in Example 1 is shown.
[0029] Figure 3 The stress-strain curve of the gel electrolyte prepared in Example 2 is shown.
[0030] Figure 4 The stress-strain curve of the gel electrolyte prepared in Example 3 is shown.
[0031] Figure 5 The stress-strain curve of the gel electrolyte prepared in Example 4 is shown.
[0032] Figure 6 The stress-strain curve of the gel electrolyte prepared in Comparative Example 2 is shown. Detailed Implementation
[0033] It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.
[0034] See Figure 1 This invention provides a schematic flowchart of an embodiment of a method for preparing a gel electrolyte, the method comprising the following steps:
[0035] Step 1: The lithium salt, polymer, polymer monomer, crosslinking agent, thermal initiator, and ionic liquid are mixed at room temperature and stirred until completely dissolved to obtain a precursor solution. Preferably, the ionic liquid is selected from one or more imidazole ionic liquids, such as one or more of 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-vinyl-3-methylimidazolium tetrafluoroborate, and 1-butyl-3-methylimidazolium hexafluorophosphate.
[0036] This step achieves macroscopic homogeneous mixing and microscopic dissolution of all components, forming a homogeneous reaction precursor. The ionic liquid serves as the sole solvent, without the addition of any organic solvent, and is used to dissolve the lithium salt, polymer monomers, crosslinking agents, and thermal initiators, while simultaneously dispersing or dissolving the polymer. Uniform stirring ensures that all components are evenly distributed at the molecular level, providing a homogeneous system for subsequent polymerization and avoiding incomplete polymerization or performance differences caused by uneven local concentrations. Complete dissolution is a prerequisite for successful polymerization; the presence of undissolved particles will affect the uniformity and mechanical properties of the gel.
[0037] Furthermore, the precursor solution comprises 10% to 40% lithium salt, 0.1% to 5% high molecular weight polymer, 1% to 30% polymer monomer, 0.01% to 0.1% crosslinking agent, 0.1% to 2% initiator, and the remainder is ionic liquid.
[0038] Step 2: Inject the precursor solution obtained in Step 1 into a mold. Preferably, the mold can be a flat plate, a battery casing, or other customized shape, allowing the gel electrolyte to be formed into a thin film, a disc, or a shape directly attached to the electrode. Injecting into the mold avoids volume shrinkage or interface defects that may occur when polymerizing directly inside the battery, facilitating the obtaining of a self-supporting gel film with uniform thickness and a smooth surface. This, in turn, facilitates the subsequent formation of the gel electrolyte with specific geometries and dimensions.
[0039] Step 3: The mold containing the precursor solution is placed in an oven at 40℃~100℃ for thermally initiated polymerization to obtain a gel electrolyte with a chemically cross-linked network, in which the ionic liquid is dispersed. In this step, the liquid precursor is transformed into a solid gel through thermally initiated free radical polymerization, forming a three-dimensional chemically cross-linked network. The specific reaction mechanism is as follows: the thermal initiator decomposes at the oven temperature to generate free radicals, which initiate chain growth and cross-linking reactions of the double bonds of the polymer monomers and cross-linking agents; during polymerization, the polymer monomers form the polymer backbone, and the cross-linking agent connects the different backbones to construct a three-dimensional network structure. The polymer does not undergo chemical cross-linking in this process, but it interpenetrates with the chemical network through physical entanglement or hydrogen bonds, enhancing the gel's toughness and structural stability. The ionic liquid and lithium salt are physically locked in the network pores, forming ionic conductive pathways. Oven heating provides a uniform temperature field, ensuring that the polymerization reaction proceeds synchronously throughout the mold and avoiding local overheating or incomplete reaction.
[0040] Furthermore, the polymer monomers include one or more of the following: acrylamide, N-hydroxyethylacrylamide, acrylic acid, methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, 2,2,2-trifluoroethyl-methacrylate, 2,2,3,3,3-pentafluoropropyl-methacrylate, 2-methoxyethyl acrylate, glycidyl methacrylate, dimethyl vinyl phosphate, diethyl vinyl phosphate, and dibutyl vinyl phosphate. The polymer monomers, as the main reactants in free radical polymerization, undergo chain-growth polymerization under the action of an initiator, forming linear or branched polymer chains that constitute the backbone of the chemical network. They also provide the main structure of the chemical cross-linking network in the final gel electrolyte; determine the basic physicochemical properties of the gel (such as hydrophilicity / hydrophobicity, glass transition temperature, etc.); their side groups (such as amide groups and ester groups) can participate in lithium ion coordination, promoting ion conduction; additionally, they can release phosphorus free radicals at high temperatures to capture ∙OH / ∙H, generating a polyphosphate carbon layer to isolate oxygen.
[0041] Furthermore, the crosslinking agent includes one or more of N,N'-methylenebisacrylamide, polyethylene glycol diacrylate, and glutaraldehyde. As a multifunctional reactant, the crosslinking agent's multiple polymerizable double bonds connect monomer chains into a network during polymerization, forming multiple crosslinking points and constructing a three-dimensional network structure, thereby preventing polymer dissolution or flow. This allows for control of the crosslinking density in the prepared gel electrolyte, directly affecting the gel's mechanical strength, swelling behavior, ion transport channel size, and thermal stability; a higher crosslinking density results in a harder and more brittle gel, but also enhanced resistance to dendrite formation.
[0042] Furthermore, the polymer comprises one or more of polyethylene oxide, polyethylene glycol, polyacrylic acid, and polyvinyl alcohol. The polymer acts as a physical framework or template, not participating in chemical cross-linking reactions, but engaging in physical entanglement or hydrogen bonding interactions with the forming chemical network, assisting in the construction of a semi-interpenetrating network structure. In the final gel electrolyte, the polymer permeates the chemical network but is not covalently linked to it, forming a physical-chemical dual network, significantly enhancing the gel's mechanical strength and toughness, improving tear and puncture resistance; regulating the gel's flexibility and elasticity; and potentially promoting lithium-ion transport through polar groups.
[0043] Furthermore, the thermal initiator comprises one or more of azobisisobutyronitrile, ammonium persulfate, potassium persulfate, and tert-pentyl peroxide. Under heating conditions, the thermal initiator decomposes to generate primary free radicals, initiating the free radical polymerization reaction of the polymer monomers and crosslinking agents. After the reaction is completed, it is consumed or leaves a small amount of inert product, which does not affect the final properties. The reaction is initiated at an appropriate temperature, and its dosage controls the polymerization rate and molecular weight distribution, thereby controlling the polymerization speed and extent to ensure uniform network formation.
[0044] Furthermore, the lithium salt comprises one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluoroborate oxalate, lithium dioxalate borate, and lithium 4,5-dicyano-2-trifluoromethylimidazolium. Lithium salts dissolve in ionic liquids, dissociating into lithium ions and anions. Although they do not participate in polymerization reactions, they influence the ionic strength and viscosity of the ionic liquid. As a high-dielectric-constant solvent, the ionic liquid promotes lithium salt dissociation and also contributes to ionic conductivity, forming a highly efficient lithium-ion transport medium. In gel electrolytes, lithium salts provide freely moving lithium ions and are the core source of ionic conductivity; the lithium salt concentration affects ionic conductivity and lithium-ion transport number. Ionic liquids, as permanent liquid phase components, provide continuous ion transport channels; they impart non-flammability, high thermal stability, and a wide electrochemical window to gel electrolytes; their polar groups facilitate lithium salt dissociation.
[0045] Furthermore, in step 1, the stirring time is 10 minutes to 12 hours. When the selected polymer has a large molecular weight or low solubility, a longer stirring time is required to achieve complete dissolution and ensure the homogeneity of the precursor solution.
[0046] Furthermore, in step 3, the baking time is from 30 minutes to 6 hours.
[0047] Furthermore, to better illustrate the process and effects of a method for preparing a gel electrolyte, the following detailed examples are provided:
[0048] Example 1
[0049] Step 1: Mix 0.1g polyethylene oxide, 5g acrylamide, 0.1g dimethyl vinyl phosphate, 0.01g N,N'-methylenebisacrylamide, 0.2g azobisisobutyronitrile, 3g lithium bis(trifluoromethanesulfonyl)imide and 20g 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt at room temperature and stir for 2 hours until all components are completely dissolved to obtain a clear and transparent precursor solution.
[0050] Step 2: Inject the precursor solution obtained in Step 1 into a glass mold.
[0051] Step 3: Place the mold in an oven at 80°C and bake for 2 hours to obtain the gel electrolyte.
[0052] Example 2
[0053] Step 1: Mix 1g polyethylene glycol, 2g methyl acrylate, 5g N-hydroxyethyl acrylamide, 0.2g diethyl vinyl phosphate, 0.005g N,N'-methylenebisacrylamide, 0.1g ammonium persulfate, 4g lithium bis(trifluoromethanesulfonyl)imide, 2g lithium bis(fluorosulfonyl)imide, 0.5g lithium tetrafluoroborate, 5g 1-vinyl-3-methylimidazolium tetrafluoroborate, and 5g 1-butyl-3-methylimidazolium hexafluorophosphate at room temperature and stir for 30 minutes until all components are completely dissolved to obtain a clear and transparent precursor solution.
[0054] Step 2: Inject the precursor solution obtained in Step 1 into a glass mold.
[0055] Step 3: Place the mold in an oven at 60°C and bake for 2 hours to obtain the gel electrolyte.
[0056] Example 3
[0057] Step 1: Mix 0.1g polyacrylic acid, 1g polyethylene glycol, 2g methyl methacrylate, 5g glycidyl methacrylate, 0.2g diethyl vinyl phosphate, 0.005g N,N'-methylenebisacrylamide, 0.1g potassium persulfate, 6g lithium bis(trifluoromethanesulfonyl)imide, 3g lithium bis(fluorosulfonyl)imide, 0.5g lithium tetrafluoroborate, 5g 1-butyl-3-methylimidazolium chloride, and 5g 1-butyl-3-methylimidazolium tetrafluoroborate at room temperature and stir for 12 hours until all components are completely dissolved to obtain a clear and transparent precursor solution.
[0058] Step 2: Inject the precursor solution obtained in Step 1 into a glass mold.
[0059] Step 3: Place the mold in an oven at 60°C and bake for 4 hours to obtain the gel electrolyte.
[0060] Example 4
[0061] Step 1: Mix 0.5g polyethylene glycol, 3g 2,2,2-trifluoroethyl-methacrylate, 2g 2-methoxyethyl acrylate, 0.1g diethyl vinyl phosphate, 0.1g dibutyl vinyl phosphate, 0.005g N,N'-methylenebisacrylamide, 0.1g azobisisobutyronitrile, 0.2g lithium difluoroborate oxalate, 1g lithium 4,5-dicyano-2-trifluoromethylimidazolium, 1g lithium difluorosulfonylimide, and 10g 1-butyl-3-methylimidazolium tetrafluoroborate at room temperature and stir for 0.5h until all components are completely dissolved to obtain a clear and transparent precursor solution.
[0062] Step 2: Inject the precursor solution obtained in Step 1 into a glass mold.
[0063] Step 3: Place the mold in an oven at 80°C and bake for 6 hours to obtain the gel electrolyte.
[0064] Performance testing was conducted on the gel electrolytes prepared in Examples 1-4.
[0065] Mechanical performance testing
[0066] Tensile tests were conducted using a universal testing machine, and the results showed that the gel electrolyte of the present invention exhibits extremely high elongation at break and tensile strength, as well as ultra-high toughness.
[0067] Flame retardant performance test
[0068] The gel electrolytes prepared in Examples 1-4 were burned with a lighter for 2 seconds. After the heat source was removed, the samples immediately self-extinguished without flame spread, demonstrating excellent flame retardant properties.
[0069] Battery safety performance test
[0070] Using the gel electrolyte prepared in Examples 1-4 as the electrolyte, and lithium manganese iron phosphate / NCM523 composite material as the positive electrode and graphite as the negative electrode, batteries were fabricated using a pouch cell process. The batteries underwent nail penetration testing, and the results showed that none of the batteries emitted smoke or swelled after being punctured, demonstrating extremely high safety.
[0071] Comparative Example 1
[0072] A commercially available electrolyte (1M LiPF6 in EC / DMC / EMC) was used, with lithium manganese iron phosphate / NCM523 composite material as the positive electrode and graphite as the negative electrode. The battery was fabricated using a pouch cell process. A nail penetration test was performed on the battery, and the results showed that after 2 seconds of penetration, the battery immediately emitted a large amount of white smoke and rapidly expanded.
[0073] Comparative Example 2 (without using polymers)
[0074] Step 1: Mix 5g acrylamide, 0.1g dimethyl vinyl phosphate, 0.01g N,N'-methylenebisacrylamide, 0.2g azobisisobutyronitrile, 3g lithium bis(trifluoromethanesulfonyl)imide, and 20g 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt at room temperature and stir for 2 hours until all components are completely dissolved to obtain a clear and transparent precursor solution. The difference between this comparative example and Example 1 is that no polymer (polyethylene oxide) was added.
[0075] Step 2: Inject the precursor solution obtained in Step 1 into a glass mold.
[0076] Step 3: Place the mold in an oven at 80°C and bake for 2 hours to obtain the gel electrolyte.
[0077] (1) Mechanical property testing: Tensile tests were conducted using a universal testing machine. The results showed that the material fractured when the strain reached 700%, and the corresponding tensile strength (fracture strength) was approximately 3.9 MPa. See Figure 6 The mechanical properties diagram shown.
[0078] (2) Flame retardant performance test: The gel electrolyte was burned with a lighter for 2 seconds. After the fire source was removed, the sample self-extinguished without flame spread. The flame retardant performance was comparable to that of Example 1.
[0079] (3) Battery safety performance test: Using lithium manganese iron phosphate / NCM523 composite material as the positive electrode and graphite as the negative electrode, a soft-pack battery was assembled using the gel electrolyte of Comparative Example 2 and subjected to a nail penetration test. The results showed that the battery did not smoke or expand after being punctured, but the voltage dropped rapidly, and the capacity decay accelerated significantly during the cycle test.
[0080] Comparative Example 2, compared to Example 1, lacked only the polymer component. The results showed that the absence of the polymer significantly reduced the mechanical strength of the gel electrolyte, indicating that the semi-interpenetrating network structure formed by the physical entanglement of the polymer is crucial for improving the gel's toughness and puncture resistance. Although flame retardancy and basic safety performance were maintained, the deterioration of mechanical properties severely affected the battery's reliability under dynamic operating conditions and failed to effectively suppress lithium dendrite puncture.
[0081] Comparative Example 3 (using organic solvents instead of ionic liquids)
[0082] Step 1: Mix 0.1g polyethylene oxide, 5g acrylamide, 0.1g dimethyl vinyl phosphate, 0.01g N,N'-methylenebisacrylamide, 0.2g azobisisobutyronitrile, 3g lithium bis(trifluoromethanesulfonyl)imide, and 20g a mixed solvent of ethylene carbonate / dimethyl carbonate / ethyl methyl carbonate (EC / DMC / EMC, volume ratio 1:1:1) at room temperature and stir for 2 hours until all components are completely dissolved to obtain a clear and transparent precursor solution. The difference between this comparative example and Example 1 is that a conventional carbonate-based organic solvent (EC / DMC / EMC) is used instead of the ionic liquid (1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt).
[0083] Step 2: Inject the precursor solution obtained in Step 1 into a glass mold.
[0084] Step 3: Place the mold in an oven at 80°C and bake for 2 hours to obtain the gel electrolyte.
[0085] (1) Mechanical property test: The gel plasticity result is poor, and it cannot form an effective shape, so it cannot be tested.
[0086] (2) Flame retardant performance test: The gel electrolyte was burned with a lighter for 2 seconds. After the flame source was removed, the sample continued to burn with obvious flame spread until it was completely burned, showing strong flammability. The flame retardant performance was much worse than that of Example 1.
[0087] (3) Battery safety performance test: Using lithium manganese iron phosphate / NCM523 composite material as the positive electrode and graphite as the negative electrode, a soft-pack battery was assembled using the gel electrolyte of Comparative Example 3 and subjected to a nail penetration test. The results showed that the battery started to smoke about 3 seconds after being punctured, and then rapidly expanded and caught fire, indicating extremely poor safety.
[0088] Compared with Example 1, Comparative Example 3 only replaced the ionic liquid with a traditional carbonate organic solvent. The results showed that: (1) the absence of the ionic liquid caused the gel electrolyte to lose its inherent flame retardancy, continued to burn under open flame, and the battery caught fire and exploded after being punctured, making its safety far inferior to Example 1; (2) the mechanical properties were very poor and could not be tested, and the sharp deterioration in safety performance made the gel electrolyte unsuitable for high-safety-requirement scenarios. It can be seen that the ionic liquid, as the only non-flammable and low-volatility solvent, is the core element for achieving the "inherent flame retardancy" and safety performance of this invention, and is irreplaceable.
[0089] Stress-strain test result analysis
[0090] Tensile tests were performed on the gel electrolytes prepared in Examples 1-4 using a universal testing machine, and the obtained stress-strain curves are shown below. Figure 2-5 As shown, the specific analysis is as follows:
[0091] Figure 2 The figure shows the stress-strain curve of the gel electrolyte in Example 1. As can be seen from the figure, the material exhibits significant structural hardening characteristics during stretching, with stress continuously increasing with strain. The material fractures at 450% strain, with a corresponding tensile strength (fracture strength) of approximately 11.5 MPa. This ultimate elongation at break exceeding 450% indicates that the gel network structure described in this example possesses excellent flexibility, while the high fracture strength of 11.5 MPa demonstrates that it maintains strong internal bonding even under high deformation. This example achieves a balance between high strength and moderate ductility.
[0092] Figure 3 The figure shows the stress-strain curve for the gel electrolyte in Example 2. As can be seen, it exhibits extremely high rigidity in the initial tensile stage, with stress rapidly increasing with strain to a peak of approximately 16 MPa. Subsequently, the material enters the yielding stage, where the stress slightly decreases and remains at a high plateau above 14 MPa, demonstrating excellent energy dissipation capabilities. Finally, the material fractures when the strain reaches approximately 90%. This curve indicates that Example 2 possesses high strength and toughness, making it suitable for battery encapsulation scenarios requiring resistance to instantaneous impacts or localized high voltages.
[0093] Figure 4 The figure shows the stress-strain curve of the gel electrolyte in Example 3. As can be seen from the figure, it exhibits high rigidity in the initial tensile stage, with stress rapidly increasing with strain to a peak of approximately 15 MPa. The material undergoes sudden fracture when the strain reaches approximately 50%, exhibiting typical brittle fracture characteristics. This indicates that the formulation design of this example endows the material with extremely high tensile strength, but relatively limited ductility, making it suitable for specific battery structure applications requiring extremely high dimensional stability and minimal deformation.
[0094] Figure 5 The figure shows the stress-strain curve for the gel electrolyte in Example 4. As can be seen, the stress rapidly increases to approximately 16 MPa within the 0-10% strain range, and then remains at a high level of 14-15 MPa within the 10-80% strain range, exhibiting excellent energy dissipation capabilities. Fracture only occurs when the strain approaches 90% (i.e., elongation at break > 800%). This example achieves a balance between high strength (16 MPa) and ultra-high ductility (> 800%), making it the best in terms of overall mechanical properties among the four examples.
[0095] Analysis of the stress-strain curves of Examples 1–4 shows that the mechanical properties of the gel electrolyte of the present invention can be flexibly controlled by the type and proportion of the formulation components. Examples 1 and 2 respectively demonstrate strain hardening and yield-hardening, two typical mechanical behaviors of polymeric elastomers, balancing strength and toughness. Example 3 achieved the highest rigidity by increasing the crosslinking density, but its ductility was limited. Example 4 is particularly outstanding, employing a combination of fluorinated monomers (TFEMA) and functional phosphate monomers (VPD / VBD), along with an appropriate amount of polymer (PEG) to form a semi-interpenetrating network structure. This successfully achieved a synergistic improvement in tensile strength up to 16 MPa and elongation at break exceeding 800%, demonstrating comprehensive mechanical properties surpassing existing technologies and laying a solid material foundation for the application of highly safe flexible lithium-ion batteries.
[0096] A comprehensive comparison of Examples 1-4 and Comparative Examples 1-3 reveals that: polymers are key components for constructing semi-interpenetrating networks and enhancing mechanical strength; the absence of this component significantly reduces the toughness of the gel electrolyte, failing to effectively suppress lithium dendrite penetration. Ionic liquids are the core solvents for achieving inherent flame retardancy and safety performance; however, the use of traditional organic solvents makes the gel electrolyte highly flammable, causing the battery to catch fire and explode during nail penetration tests, thus failing to resolve safety issues. Only by simultaneously employing polymers and ionic liquids, supplemented with optimized formulation ratios (as in Example 4), can a synergistic improvement in mechanical strength (>16MPa), ductility (>800%), flame retardancy (self-extinguishing in open flame), and electrochemical performance be achieved, meeting the stringent requirements of next-generation high-safety lithium-ion batteries.
[0097] The above are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. All equivalent structural transformations made using the contents of the present invention's specification and drawings under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.
Claims
1. A method for preparing a gel electrolyte, characterized in that, The method includes the following steps: Step 1: Lithium salt, polymer, polymer monomer, crosslinking agent, thermal initiator, and ionic liquid are mixed at room temperature and stirred until completely dissolved to obtain a precursor solution. The ionic liquid includes one or more imidazole-based ionic liquids. The precursor solution does not contain organic solvents. The polymer includes one or more of polyethylene oxide, polyethylene glycol, polyacrylic acid, and polyvinyl alcohol. The polymer monomer includes one or more of acrylamide, N-hydroxyethylacrylamide, acrylic acid, methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, 2,2,2-trifluoroethyl-methacrylate, 2,2,3,3,3-pentafluoropropyl-methacrylate, 2-methoxyethyl acrylate, and glycidyl methacrylate. Step 2: Inject the precursor solution obtained in Step 1 into the mold; Step 3: Place the mold containing the precursor solution in an oven at 40℃~100℃ for thermally initiated polymerization to obtain a gel electrolyte with a chemical cross-linked network. In the precursor solution, the polymer monomers form a chemical cross-linked network through thermal initiation. The polymer and the chemical cross-linked network form a semi-interpenetrating polymer network through physical entanglement or hydrogen bonding. The ionic liquid and lithium salt are distributed in the pores of the chemical cross-linked network.
2. The method as described in claim 1, characterized in that, In step 1, the precursor solution comprises 10% to 40% lithium salt, 0.1% to 5% polymer, 1% to 30% polymer monomer, 0.01% to 0.1% crosslinking agent, 0.1% to 2% initiator, and the remainder is ionic liquid.
3. The method as described in claim 2, characterized in that, The lithium salts include one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluoroborate oxalate, lithium dioxalate borate, and lithium 4,5-dicyano-2-trifluoromethylimidazolium.
4. The method as described in claim 1, characterized in that, Crosslinking agents include one or more of N,N'-methylenebisacrylamide, polyethylene glycol diacrylate, and glutaraldehyde.
5. The method as described in claim 1, characterized in that, The thermal initiator includes one or more of azobisisobutyronitrile, ammonium persulfate, potassium persulfate, and tert-pentyl peroxide.
6. The method as described in claim 1, characterized in that, In step 1, the stirring time is 10 minutes to 12 hours; in step 3, the baking time is 30 minutes to 6 hours.
7. A gel electrolyte, characterized in that, The electrolyte is prepared by the method according to any one of claims 1-6.
8. A lithium-ion battery, characterized in that, The lithium-ion battery comprises the gel electrolyte as described in claim 7.
Citation Information
Patent Citations
Flame-retardant flexible composite gel electrolyte material and preparation method and application thereof
CN115207461A
Gel solid electrolyte, preparation method thereof and lithium ion battery
CN120319881A